COMMUNITY OF METAZOAN PARASITES OF CORVINA DRUM CILUS GILBERTI (ABBOTT, 1899) (PERCIFORMES: SCIAENIDAE) IN THE COASTAL ZONE OF CHORRILLOS, LIMA, PERU - Chero, Jhon (2014)
The corvina drum Cilus gilberti (Abbott, 1899) (Sciaenidae), is a demersal and carnivorous species distributed from Sechura Bay (Peru) to Lot (Chile). This work represents a qualitative and quantitative analysis of C. gilberti parasite communities in Peru, with the aim of assessing their metazoan parasite community in the coastal area of Chorrillos, Lima, Peru. One hundred and three specimens of C. gilberti were acquired in Fishing Terminal Chorrillos, Lima, Peru from August to October 2011. The parasites were collected, fixed, preserved and quantified using standard procedures. Atotal of 257 parasites and 16 parasite species were collected. The highest frequency of dominance and relative dominance were three endoparasites: Diphyllobothrium pacificum, a Philometridae species and Corynosoma obtuscens. The prevalence and mean abundance of D. pacificum were correlated with the total length of the host. Parasitefauna of C. gilberti showed relatively high values of alpha diversity indices but indices of dominance had low values. Nonparametric estimators indicated no effort to increase the sampling of fish hosts. The index of interactivity (CC ) showed high values indicating that parasite communities are isolated or non- 50 interactive. The parasite community of C. gilberti did not follow any of the four theoretical models of patterns of abundance-diversity. All parasites recorded, except: Lernanthropus pacificus; Neobrachiella sp.; Helicometra fasciata; Villarrealina peruviana and D. pacificum are considered new records for C. gilberti in Peru. The discovery of the plerocercoid of D. pacificum in corvina drum indicates that this host species has zoonotic potential in the central Peruvian coast. Plagioporus sp. and Raphidascaris sp. are recorded for the first time on the Peruvian coast.